The hypothalamic effects of PACAP on the hypothalamic-pituitary-gonadal axis in male mice - Faludi, Péter; Barabás, Klaudia; Lengyel, Ferenc; Udvarácz, Ildikó; Pham, Dániel; Kisjós, Olivér; Nagy, Zsuzsanna; Reglődi, Dóra; Kovács, Gergely (Frontiers in Endocrinology, 2025)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is a member of the vasoactive intestinal peptide (VIP) neuropeptide family and plays a role in the regulation of several releasing hormones and tropic hormones. The hypothalamic-pituitary-gonadal (HPG) axis governs the synthesis and the release of sex hormones and the gametogenesis in all mammals. While the effects of PACAP on fertility is well-documented in females, much less data are available in males. The aim of our study was to examine potential structural and expressional changes in the hypothalamus that might underlie the fertility deficits observed in male PACAP knockout (KO) mice. To this end, we performed immunofluorescent, immunohistochemical and RNAscope in situ hybridization stainings to detect the protein and/or mRNA expression of gonadotropin-releasing hormone (GnRH), kisspeptin, estrogen receptor alpha (ERα) and androgen receptor (AR) in the hypothalamus. Our results revealed that the number and immunoreactivity of GnRH neurons were lower in the medial preoptic area (MPOA) in PACAP KO mice. In contrast, the number of kisspeptin neurons was higher in the rostral periventricular region of the third ventricle (RP3V) and the mid arcuate nucleus (ARC). Furthermore, higher number of Esr1-positive cells was found in the kisspeptin-rich RP3V and the ARC. Notably, less AR-positive cells, and more ERα-positive cells were detected in the MPOA demonstrating a possible misbalance between estrogenic and androgenic signaling. Our results suggest that neuroendocrine changes induced by PACAP deficiency in the hypothalamus might contribute to the development of reproductive dysfunction in PACAP-deficient males by disrupting normal HPG axis function.